2011
DOI: 10.1055/s-0031-1300052
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy and Safety of Azelastine and Levocabastine Nasal Sprays in Patients with Seasonal Allergic Rhinitis

Abstract: The aim of the present investigation was to compare the efficacy and tolerability of azelastine (CAS 58581-89-8) (1.12 mg/day) and levocabastine (CAS 79547-78-7) (0.4 mg/day) nasal spray administered twice daily to patients with seasonal allergic rhinitis. A total of 180 patients participated in a 4-week, double-blind, parallel group (n = 90 each) study. Symptom severity of nasal, ocular and other symptoms were recorded, out of which a total symptom score (TSS) was calculated. Physicians assessed symptoms at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Total nasal symptom control was similar in both the LNS and ANS group (LNS 92% and ANS 93%). These results are consistent with those of other investigators [10,11] . In terms of onset of action, both LNS [10,13] and ANS [12,13] for treatment of AR had a rapid onset of effect.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Total nasal symptom control was similar in both the LNS and ANS group (LNS 92% and ANS 93%). These results are consistent with those of other investigators [10,11] . In terms of onset of action, both LNS [10,13] and ANS [12,13] for treatment of AR had a rapid onset of effect.…”
Section: Discussionsupporting
confidence: 94%
“…It is not surprising that both ANS and LNS provided effective and well-tolerated symptomatic treatment of seasonal AR [1,2] . ANS was reported to be statistically superior in efficacy as well as in safety in a 4-week treatment of 180 patients [11] , while LNS was found to be at least as effective as, but better tolerated than, ANS in a 1-week treatment of 123 patients [10] . As no direct comparison of these two topical antihistamines for the treatment of persistent AR has been undertaken to date, the present study was initiated to compare the onset of action, efficacy, and tolerability of either ANS or LNS as monotherapy for moderate-to-severe persistent AR.…”
Section: Two Topical Antihistamines In Ar Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, in Falser et al's study, 22 in which the efficacy and tolerability of Azelastine and Levocabastine nasal spray were investigated, the results showed that after four weeks of treatment with Azelastine, the mean overall total symptom score (TSS) was reduced. Global efficacy in 92% of Azelastine patients and 76% of Levocabastine patients showed that the treatment was either “very good” or “good.” Therefore, similar to our study, they concluded that Azelastine was statistically superior in efficacy as well as safety.…”
Section: Discussionmentioning
confidence: 99%
“…20 Azelastine is an intranasal antihistamine that inhibits the production or release of leukotrienes, free radicals, and cytokines. 21 Azelastine has a high binding affinity to H1 receptors and can also inhibit H2 antihistamine receptors and the synthesis or expression of mediators of allergic inflammation and neuro peptides and has a rapid onset 22 which alleviates AR bothering symptom rapidly rather than an oral antihistamine. Combining intranasal corticosteroids with Azelastine or Montelukast can improve the efficacy of moderate to severe AR treatment.…”
Section: Introductionmentioning
confidence: 99%